Impact of ZnO addition on structural, morphological, optical, dielectric and electrical performances of BaTiO3 ceramics - Slimani, Y.; Selmi, A.; Hannachi, E.; Almessiere, M. A.; Baykal, A.; Ercan, I. (Journal of materials science. Materials in electronics, 2019)
BaTiO 3 /(ZnO) x ceramics (x = 0, 2, 5 and 10 wt%) were produced via solid state reaction by using high energy ball milling. The morphological, structural, spectral, optical, electrical and dielectric properties were systematically investigated. X-ray diffraction indicated that all ceramics crystallize in the tetragonal structure. The grains size increases with ZnO additions. The optical band gap energy (E g ) was also evaluated and found to reduce with increasing ZnO concentration. The dielectric and electric properties revealed that an optimal ZnO content lead to obtain ceramic with high dielectric constant and low tangent loss, which are encouraging for radio frequencies and microwaves applications.